2009
DOI: 10.1007/s10926-009-9220-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Employers’ Hiring Intentions in Relation to Qualified Workers with Disabilities: Preliminary Findings

Abstract: The themes derived from this study can be used to help occupational rehabilitation professionals develop educational and marketing interventions to improve employers' attitudes toward hiring and retaining individuals with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 8 publications
1
101
1
3
Order By: Relevance
“…Additionally, studies have shown that there is uncertainty and doubt among employers when they consider hiring persons with disabilities [30][31][32], especially among employers with no experience of such hiring [33]. In a qualitative study using semi-structured interviews, employers were asked about their attitudes towards hiring people with various disabilities.…”
Section: Employers' Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies have shown that there is uncertainty and doubt among employers when they consider hiring persons with disabilities [30][31][32], especially among employers with no experience of such hiring [33]. In a qualitative study using semi-structured interviews, employers were asked about their attitudes towards hiring people with various disabilities.…”
Section: Employers' Concernsmentioning
confidence: 99%
“…According to the Swedish Work Environment Act, employers are responsible for adapting the work situation to suit their employees' individual prerequisites [35]. Investigations into employers' views on hiring people with disabilities have shown both reluctance and satisfaction [30][31][32][33]36]. However, employers' views on work ability are rarely investigated [30,32,36].…”
Section: Employers' Concernsmentioning
confidence: 99%
“…Fraser et al [13] cogently pointed out that the unemployment and underemployment problem of people with disabilities cannot be addressed by changing employer attitudes alone. As supported by the articles published in this special section, employers generally hold moderately positive attitudes toward people with disabilities and express a willingness to hire and retain workers with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, comme en font foi les deux études présentées dans cet article, le marché de l'emploi comporte encore des défis pour ces dernières, notamment ceux reliés à l'accessibilité des environnements de travail, à la perception que les personnes Les deux études soulignent l'importance de sensibiliser les employeurs aux réalités de la personne qui tente de se tailler une place dans un milieu de travail. Au dire des personnes ayant un handicap, les attitudes des employeurs correspondent au facteur le plus déterminant dans leur accès à l'emploi (Fraser, et collab., 2011). Or, des recherches révèlent que ces derniers entretiennent des préjugés à leur endroit (Beaton, Kabano et Léger, 2012).…”
Section: Discussionunclassified